Chiral Atropisomeric Indenocorannulene Bowls: Critique of the Cahn–Ingold–Prelog Conception of Molecular Chirality. Issue 22 (2nd May 2018) - Wang, Yujia; Allemann, Oliver; Balaban, T. Silviu; Vanthuyne, Nicolas; Linden, Anthony; Baldridge, Kim K.; Siegel, Jay S.
Abstract: Chiral corannulenes abound, but suffer generally from configurational lability associated with bowl‐to‐bowl inversion, 1 thus obviating questions of stereogenicity and stereoelement construction.2 In contrast, peri‐annulated corannulenes show greatly increased barriers for bowl‐to‐bowl inversion; specifically indenocorannulenes invert on a time scale too slow to observe by normal NMR methods and raise the possibility of creating chiral atropisomeric bowl‐shaped aromatics.3 Two methods for preparing indenocorannulene from simple 2‐haloarylcorannulenes—silyl cation C–F activation, 4 and Pd‐mediated C–Cl activation [5] —enable the synthesis of an array of such chiral atropisomeric indenocorannulenes.6 Resolution of the enantiomers by high‐performance liquid chromatography over chiral support phases motivates the study of chiroptical properties, the assignment of absolute "Cartesian" configuration, and the assessment of configurational stability.7 These studies bring into question any systematic assignment of nontrivial stereoelements (i.e. not the molecule in its entirety) and refute any assertion of congruence between "Cahn–Ingold–Prelog elements" and the physical or "Cartesian" basis of chirality. Abstract : Chirality redefined : The synthesis and resolution of chiral monosubstituted indenocorannulenes revive questions about the relationship between geometric chirality and stereoisomeric nomenclature. By comparing theoretical and experimental vibrational and electronic circular dichroism spectra, the absolute (Cartesian) configuration of these compounds can be determined independent of the specification of the stereoisomeric configuration according to Cahn–Ingold–Prelog.